Participatory Evaluation of Early Maturing Sorghum Technologies in Eastern Amhara Region of Ethiopia - Negussie Siyum; Abere Haile; Mekonenn Assefa; Mesfin Bahta (Universitas Panji Sakti, 2021)
The low or non-adoption of improved agricultural technologies might be resulted from inadequate participation of farmers at all stages of the process of benefiting farmers. The current study was conducted in the representative sorghum producing areas of Wollo i.e. Raya kobo, Kalu and Dawa chefa with the objective of assessing farmers’ preference towards improved sorghum varieties and providing a menu of sorghum technologies. The study was conducted in 2019 cropping season having one year duration. Both inferential and descriptive statistics were used to analyze the collected data. Farmers’ perception was assessed using preference ranking and narration. Moreover, Agricultural events such as field days and experience sharing were prepared to capture farmers’ perception about the technologies. GenStat v.18th was used to analyze the data. Analysis of variance was employed to test the mean difference of yield among varieties. The result of ANOVA showed that improved sorghum varieties Dekeba and ESH1 gave the highest grain yield at respective sites. In kalu and Dawa chefa, farmers preferred Argiti whereas in Raya Kobo, Melkam was the variety preferred by the farmers. From the analysis of Spearman’s rank correlation, there was evidence on coincidence of farmers’ preference and the actual data. Therefore, based on the analysis of farmers’ preference and yield data, improved sorghum technologies Melkam and Argiti can be promoted in the respective districts of the study area.